PERSONALISASI PARTAI DAN DINAMIKA ELEKTORAL GERINDRA DI KOTA DENPASAR PADA PEMILU 2024 - Teddy Chrisprimanata Putra (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study examines the phenomenon of party personalization within the Great Indonesia Movement Party (Gerindra) and its implications for the party’s electoral performance in Denpasar City during the 2024 General Election. Party personalization refers to the emergence of a dominant figure whose influence leads to the party’s dependence on a small elite. This research employs a qualitative-explanatory method, analyzing relevant literature, expert commentary, and data drawn from official documents and related articles. The findings indicate that the strong personal leadership of Prabowo Subianto, serving as both the Chairperson and the Chair of the Advisory Board of Gerindra, was the primary factor behind the party’s increased electoral gains. Prabowo’s charisma, military background, socio-economic status, and the entrenched culture of patronage further consolidated his dominance within the party. At the local level, the political stature of Made Muliawan Arya (De Gadjah), Chairperson of Gerindra’s Bali Regional Leadership Council, significantly contributed to the rise in votes in Denpasar City. In the 2024 election, Gerindra Denpasar secured 64,114 votes—an increase of 111% compared to the 2019 election—and won nine legislative seats. While party personalization can yield electoral advantages, it also poses long-term risks, including the erosion of internal democracy, leadership circulation, and policy orientation toward elite interests. Therefore, leadership regeneration is essential to ensure the sustainability of party and national democracy.